MIXED GONADAL DYSGENESIS IN A SEVEN MONTH OLD BABY - Krishna Levina, Made Ayu; Arimbawa, I Made (Medicina; Vol 45 No 1 (2014): Januari 2014, 2015)
Mixed gonadal dysgenesis is a very rare case with genital ambiguity as a clinical manifestation.Diagnosis of this condition is emerging due to proper gender assignment and  prompt treatment to achieve optimal physical and psychologic development. We reported a genital ambigous in a 7 month old baby, who was referred with enlargement of clitoris, an unpalpable testis, but with a high concentration testosteron serum level, an uterus from genitography, and a mosaic karyotype 45,X/46,XY. The working diagnosis of this baby is mixed gonadal dysgenesis. Patients is being evaluated by a multidisciplinary team and planned having laparoscopy.  [MEDICINA 2014;45:52-57]
Keywords: mixed gonadal dysgenesis, mosaic karyotype, ambiguous genitalia